An update on the utility and safety of cholinesterase inhibitors for the treatment of Alzheimer's disease. Issue 2 (1st February 2020) - Haake, Andrea; Nguyen, Kevin; Friedman, Lauren; Chakkamparambil, Binu; Grossberg, George T
ABSTRACT: Introduction : Alzheimer's disease (AD) is the most common cause of major neurocognitive disorders with a prevalence in the US of about 5.7 million in 2018. With the disease burden projected to increase dramatically in the coming years, it is imperative to review the current available treatment regimens for their safety and utility. The cholinesterase inhibitors (ChEIs) have continued to play a pivotal role in managing the symptoms and possibly slowing the rate of progression of AD since 1993. Owing to their being a mainstay in the treatment of AD, the safety and efficacy of prescribing these drugs needs to be reviewed often, especially with the approval of new formulations and doses. Areas covered : The three ChEIs currently approved by the FDA are donepezil, rivastigmine and galantamine. This article will review the safety and tolerability of these ChEIs and analyze the potential disease modifying properties of these drugs. The authors have reviewed all recent literature including review articles, meta-analyzes, clinical trials and more. Expert opinion : These ChEIs differ subtly in their mechanisms of action, in their tolerability and safety and FDA-approved indications. All are considered first-line, symptomatic treatments of the various phases of AD and may even have potentially disease-modifying effects.